2000
DOI: 10.1007/s004390000277
|View full text |Cite
|
Sign up to set email alerts
|

Association of butyrylcholinesterase K variant with cholinesterase-positive neuritic plaques in the temporal cortex in late-onset Alzheimer's disease

Abstract: In confirmed late-onset (>65 years) Alzheimer's disease, we found a greater load, both of overall neuritic plaques and of cholinesterase-positive neuritic plaques, in the temporal cortex of carriers of the butyrylcholinesterase K variant (BCHE-K) aged <80 years than of all other patients. The differences were most striking in the case of cholinesterase-positive neuritic plaques. Among BCHE-K carriers, densities of such plaques were over six times higher in patients <80 years at death than in those >80 years (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 56 publications
3
11
0
1
Order By: Relevance
“…The genotype and allele frequencies of the control samples were comparable to those reported in the literature [Lehmann et al, 2001;Mubumbila et al, 2002]. It has been suggested that the failure to replicate the significance of the K-variant, or indeed other putative risk genes, could be attributed to sampling variables for each cohort studied [Lehmann et al, 2000[Lehmann et al, , 2001. A justifiable concern regards the diagnostic criteria, as the majority of K-variant ''positive'' studies had used necropsy-confirmed cases.…”
mentioning
confidence: 56%
“…The genotype and allele frequencies of the control samples were comparable to those reported in the literature [Lehmann et al, 2001;Mubumbila et al, 2002]. It has been suggested that the failure to replicate the significance of the K-variant, or indeed other putative risk genes, could be attributed to sampling variables for each cohort studied [Lehmann et al, 2000[Lehmann et al, , 2001. A justifiable concern regards the diagnostic criteria, as the majority of K-variant ''positive'' studies had used necropsy-confirmed cases.…”
mentioning
confidence: 56%
“…Additionally, the BCHE-K variant promotes fibril formation by participating in the transformation of Aβ from an initially benign form to an eventually malignant form. The BCHE-K variant acts as a general candidate risk factor of AD (84,85). Six significant results (46-51) and 22 non-significant results (5, were found in previous studies on the association between the BCHE-K variant and AD.…”
Section: Discussionmentioning
confidence: 92%
“…Investigations of this BCHE variant have observed that its presence pre-empts progression of AD (Sandbrink et al, 1998;O'Brien et al, 2003). However, other studies have suggested that this variant is associated with AD (Tilley et al, 1999;Wiebusch et al, 1999;Lehmann et al, 2000;Lehmann et al, 2001;McIlroy et al, 2000) and still others have observed no association of BCHE-K variant with AD (Hiltunen et al, 1998;Kehoe et al, 1998;Singleton et al, 1998;Grubber et al, 1999;Ki et al, 1999;Yamamoto et al, 1999). This suggests that the role(s) of BChE in AD may involve other components of the disease and requires further scrutiny.…”
Section: Introductionmentioning
confidence: 86%